A Study on Major Components of Bee Venom Using Electrophoresis - Lee, Jin-Seon; Kwon, Gi-Rok; Lee, Seung-Bae (Korean Pharmacopuncture Institute, 2000)
This study was designed to study on major components of various Bee Venom(Bee Venom by electrical stimulation in Korea; K-BV I, Bee Venom by Microwave stimulation in Korea; K -BV II, 0.5rng/ml, Fu Yu Pharmaceutical Factory, China; C-BV, 1mg /ml, Monmouth Pain Institute, Inc., U.S.A.; A-BV) using Electrophoresis. The results were summarized as follows: 1. In 1:4000 Bee Venom solution rate, the band was not displayed distinctly usmg Electrophoresis. But in 1: 1000, the band showed clearly. 2. The results of Electrophoresis at solution rate 1:1000, K-BV I and K-BVII showed similar band. 3. The molecular weight of Phospholipase A2 was known as 19,000 but its band was seen at 17,000 in Electrophoresis. 4. Protein concentration of Bee Venom by Lowry method was different at solution rate 1:4000 ; C-BV was 250μg/ml, K-BV I was 190μg/ml, K-BV Ⅱ was 160μg/ml and C-BV was 45μg/ml. 5. Electrophoresis method was unuseful for analysis of Bee Venom when solution rate is above 1:4000 but Protein concentration of Bee Venom by Lowry method was possible. These data from the study can be applied to establish the standard measurement of Bee Venom and prevent pure bee venom from mixing of another components. I think it is desirable to study more about safety of Bee Venom as time goes by.